Adverse reactions to biologics - Puig Sanz, Lluís; Gulliver, Wayne (Current problems in dermatology / series editors Peter Itin, Gregor B.E. Jemec, 2018)
In many areas of medicine physicians still face the great challenge of finding therapies that will meet the patients' needs. In dermatology the challenge has arisen on multiple fronts through advances in the understanding of the immunopathogenesis of many inflammatory and malignant cutaneous disorders. Breakthroughs, combined with significant developments in targeted immunotherapy, have resulted in improved outcomes as these newer therapies are being used for both approved indications and as off-label therapies for various chronic inflammatory skin disorders and many forms of skin cancer. In the expectation that by truly understanding the safety profile of these targeted therapies patients' outcomes will be significantly improved, this book offers insights into topics such as adverse reactions, infectious complications and the perioperative use of biologics in psoriasis, immunogenicity of biologic therapies, paradoxical reactions, safety of biologics used to treat autoimmune bullous diseases and primary cutaneous lymphomas, adverse reactions and skin manifestations of therapies targeting melanoma and non-melanoma skin cancer and other neoplastic diseases. Eminent researchers with extensive clinical experience have contributed to this publication, providing an in-depth overview of the latest knowledge in this field.